USA Policy Toward Terrorism - Mustafić, Mevludin (Kriminalističke teme, 2005)
Essay analyzes United States of America policy toward terrorism. Global fight against international terrorism in essay is presented as a war for new territories and colonies from which natural welfares will be dipper, especially oil. There are examples, stated by American political scientists, that USA “leading terrorist country'' in the world that produces violence beyond the framework of international law, diplomacy and war and with USA stays without reach of any norms of international law in which USA should be suspected for international terrorism (like in case of Nicaragua) . Together with that, USA is only country suspected by World Court for producing international terrorism, today presented in transparent examples, and all of that under global antiterrorist activity in the world.